Mengeksplorasi Potensi Dan Risiko Perdagangan Bebas Indonesia-Vietnam Pada Komoditas Pertanian Lada - Nur Widyawati; Sinta Istamarina; Khiarotunisa; Amanda Prita Padila; Daspar (Jurnal Ekonomi dan Bisnis Digital, 2024)
Amid declining export demand from major markets, Indonesia needs to shift its attention to alternative markets. Vietnam emerged as a promising option to expand the reach of exports, in the context of flour. The study aims to assess the potential and seriousness of the Vietnamese flour trade market, as well as identify the tax and non-customs barriers seen in the commodity cycle there. The UN-Comtrade trade database and the World Integrated Trade Solution (WITS) provide data used for the years 2010 to 2019. The investigative technique applied is RCA or Uncovered Relative Benefit. The results of the study show that the coordination of trade between Indonesia and Vietnam is still weak, and the importance of Indonesian flour in the Vietnamese market remains weak. Under another state. Indonesian flour exports to Vietnam are also affected by significant non-tariff barriers. Productivity is also a major factor affecting a country's export capacity. To increase the added value of Indonesian flour products, it is necessary to pay attention to the aspects of quality and diversification of products. Therefore, an integrated policy is needed that covers the entire production and distribution chain, including cultivating seed and creation properties, pesticide protection efforts, cultivating the nature of management enterprises, increasing the productivity of creation costs, and fostering political participation both provincially and multilaterally.